Neuromuscular Adaptations to Same-Session Combined Endurance and Strength Training in Recreational Endurance Runners - Schumann, M.; Pelttari, P.; Doma, K.; Karavirta, L.; Häkkinen, K. (International Journal of Sports Medicine, 2016)
This study examined neuromuscular adaptations in recreational endurance runners during 24 weeks of same-session combined endurance and strength training (E+S, n=13) vs. endurance training only (E, n=14). Endurance training was similar in the 2 groups (4–6x/week). Additional maximal and explosive strength training was performed in E+S always after incremental endurance running sessions (35–45 min, 65–85% HRmax). Maximal dynamic leg press strength remained statistically unaltered in E+S but decreased in E at week 24 (−5±5%, p=0.014, btw-groups at week 12 and 24, p=0.014 and 0.011). Isometric leg press and unilateral knee extension force, EMG of knee extensors and voluntary activation remained statistically unaltered in E+S and E. The changes in muscle cross-sectional (CSA) differed between the 2 groups after 12 (E+S+6±8%, E −5±6%, p<0.001) and 24 (E+S+7±7%, E −6±5%, p<0.001) weeks. 1 000 m running time determined during an incremental field test decreased in E+S and E after 12 (−7±3%, p<0.001 and −8±5%, p=0.001) and 24 (−9±5%, p=0.001 and −13±5%, p<0.001) weeks. Strength training performed always after an endurance running session did not lead to increased maximal strength, CSA, EMG or voluntary activation. This possibly contributed to the finding of no endurance performance benefits in E+S compared to E.
Keywords: concurrent training; EMG; voluntary activation; muscle cross-sectional-area; endurance running